Wrong schools or wrong students? The potential role of medical education in regional imbalances of the health workforce in the United Republic of Tanzania - Riise Kolstad Julie; Leon Beatus K (BMC, 2010)
Abstract Background The United Republic of Tanzania, like many other countries in sub-Saharan Africa, faces a human resources crisis in its health sector, with a small and inequitably distributed health workforce. Rural areas and other poor regions are characterised by a high burden of disease compared to other regions of the country. At the same time, these areas are poorly supplied with human resources compared to urban areas, a reflection of the situation in the whole of Sub-Saharan Africa, where 1.3% of the world's health workforce shoulders 25% of the world's burden of disease. Medical schools select candidates for training and form these candidates' professional morale. It is therefore likely that medical schools can play an important role in the problem of geographical imbalance of doctors in the United Republic of Tanzania. Methods This paper reviews available research evidence that links medical students' characteristics with human resource imbalances and the contribution of medical schools in perpetuating an inequitable distribution of the health workforce. Existing literature on the determinants of the geographical imbalance of clinicians, with a special focus on the role of medical schools, is reviewed. In addition, structured questionnaires collecting data on demographics, rural experience, working preferences and motivational aspects were administered to 130 fifth-year medical students at the medical faculties of MUCHS (University of Dar es Salaam), HKMU (Dar es Salaam) and KCMC (Tumaini University, Moshi campus) in the United Republic of Tanzania. The 130 students represented 95.6% of the Tanzanian finalists in 2005. Finally, we apply probit regressions in STATA to analyse the cross-sectional data coming from the aforementioned survey. Results The lack of a primary interest in medicine among medical school entrants, biases in recruitment, the absence of rural related clinical curricula in medical schools, and a preference for specialisation not available in rural areas are among the main obstacles for building a motivated health workforce which can help correct the inequitable distribution of doctors in the United Republic of Tanzania. Conclusion This study suggests that there is a need to re-examine medical school admission policies and practices.